Students of Primary Education Degree from two European universities: a competency-based assessment of performance in multigrade schools. Comparative study between Spain and Slovenia - Magro Gutiérrez, Montserrat; Hus, Vlasta; Jančič Hegediš, Polona; Carrascal Domínguez, Silvia (Revista Española de Educación Comparada, 2021)
The success of teaching in multigrade contexts demands that teachers have the knowledge and skills considered necessary to enhance the pedagogical possibilities of these environments. This quantitative, descriptive and non-experimental study explores the extent to which students in the Primary Education Degree in two European universities, one in Spain and one in Slovenia, feel prepared to teach in a multigrade school, based on the training they have received. The results show a relationship between the level of confidence students have in the training received for multigrade performance and differences in the levels of confidence acquired in the competencies assessed. The conclusions emphasise the need to develop university training experiences that contribute to the development of the required teaching skills.